Options to enhance the veracity of Australian health service accreditation assessments. Issue 2 (May 2022) - Hinchcliff, Reece; Debono, Deborah; Carter, David; Glennie, Miriam; Robertson, Hamish; Travaglia, Joanne
Background: Assessment processes applied within some health service accreditation programs have been criticised at times for being inaccurate, inconsistent or inefficient. Such criticism has inspired the development of innovative assessment methods. Objective: The Australian Commission on Safety and Quality in Health Care considered the use of three such methods: short-notice or unannounced methods; patient journey or tracer methods; and attestation by governing bodies. Method: A systematic search and synthesis of published peer-reviewed and grey literature associated with these methods. Results and Conclusion: The published literature demonstrates that the likely benefits of these three assessment methods warrant further evaluation, real-world trials and stakeholder consultation to determine the most appropriate models to introduce into national accreditation programs. Implications: The subsequent introduction of models of short-notice assessments and attestation by governing bodies into the Australian Health Service Safety and Quality Accreditation Scheme in January 2019 demonstrates how the findings presented in this article influenced the national change in assessment practice, providing an example of evidence-informed accreditation development.